(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2024)
The main aim of the article is to assess the diversity of tourist attractiveness of the districts of Middle Pomerania located outside the Baltic Sea Coast. The subject of the research are poviats, excluding city counties and those in which there are coastal communes, because they are developing more dynamically than the rest of the region. Data were obtained from the Central Statistical Office for 2014 and 2020, from the Local Data Bank. A multidimensional analysis using synthetic measures was used to assess tourist attractiveness. The level of tourist attractiveness was determined on the basis of three sections: natural environment, cultural heritage and tourist infrastructure. Partial indicators were assigned to each section. The analyzes conducted show that the studied counties are characterized by diversity in terms of tourist attractiveness, which influences the directions of their development.